The influence of ambient air pollution on health impacts: The Project FUTURAR preliminary results - Mendes, Ana Sofia (2022)
The main goal of FUTURAR Project is to estimate the air pollution impact, costs and benefits of emission reduction scenarios for 2030, using modelling tools to estimate the spatial distribution of environment and health impacts over Portugal. This research will support strategies on air pollution mitigation allowing to fill knowledge gaps and adjust/tune/improve estimates of emissions reduction and consequently environment and health impacts for Portugal, by providing information on key uncertainties and research needs